A "Phenolic" Off-odour in White Table Wines: Causes and Methods to Diminish its Occurrence - van Wyk, C.J.; Rogers, l.M. (South African Journal of Enology and Viticulture, 2017)
The quality of some Kerner table wines often is rated inferior owing to the presence of an objectionable odour designated as "medicinal", "elastoplast" (band-aid) or "phenolic". Occasionally this odour is also encountered in wines from other cultivars such as Gewiirztraminer, Weisser Riesling, Muscat de Frontignan and Chenin blanc. The objectives of this study were to identify the compounds responsible for the off-odour and to establish possible relationships between their occurrence and vini-viticultural procedures. The component predominantly responsible for the "medicinal" odour was identified as p-vinyl guaiacol. This compound is known to be formed during alcoholic fermentation via decarboxylation of ferulic acid. Yeast strains, however, differed appreciably with respect to their ability to produce p-vinyl guaiacol. Most, if not all, of this component is apparently formed during alcoholic fermentation of grape juice. Only in one exceptional case was the presence of this odour detected in grapes from a crossing of Cruchen blanc x Servan blanc, which also contained relatively high levels of p-vinyl guaiacol. Wines made from grapes harvested at an advanced degree of maturity and in particular those exposed to sunlight, contained higher levels of p-vinyl guaiacol than did those from shaded grapes. Oxidation and subsequent treatment of grape juice with phenol-adsorbing fining agents such as activated charcoal, polyvinyl polypirrolidone, casein and gelatine (in combination with "kieselsol" and bentonite) led to decreases in the p-vinyl guaiacol levels and the concomitant "medicinal" odour intensity.